Geophysical surveys of the sediments of Loch Ness, Scotland : implications for the deglaciation of the Moray Firth Ice Stream, British-Irish Ice Sheet. - Turner, A.J.; Woodward, J.; Dunning, S.A.; Shine, A.J.; Stokes, C.R.; O'Cofaigh, C. (Journal of Quaternary Science, 2012)
We present results from three geophysical campaigns using high-resolution sub-bottom profiling to image sediments deposited in Loch Ness, Scotland. Sonar profiles show distinct packages of sediment, providing insight into the loch's deglacial history. A recessional moraine complex in the north of the loch indicates initial punctuated retreat. Subsequent retreat was rapid before stabilisation at Foyers Rise formed a large stillstand moraine. Here, the calving margin produced significant volumes of laminated sediments in a proglacial fjord-like environment. Subsequent to this, ice retreated rapidly to the southern end of the loch, where it again deposited a sequence of proglacial laminated sediments. Sediment sequences were then disturbed by the deposition of a thick gravel layer and a large turbidite deposit as a result of a jökulhlaup from the Spean/Roy ice-dammed lake. These sediments are overlain by a Holocene sheet drape. Data indicate: (i) a former tributary of the Moray Firth Ice Stream migrated back into Loch Ness as a major outlet glacier with a calving margin in a fjord-like setting; (ii) there was significant sediment supply to the terminus of this outlet glacier in Loch Ness; and (iii) that jökulhlaups are important for sediment supply into proglacial fjord/lake environments and may compose >20% of proglacial sedimentary sequences.